Transformation of Islamic Education: Fostering Exemplary Character through Integrated Curriculum in Islamic Elementary Schools - Kasmawati, Kasmawati; Herlian, Herlian; Adam, Adam; Deluma, Ridwan; Abubakar, Abubakar; Muliyani, Muliyani (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2023)
This article discusses the development of an Islamic character-based curriculum in Al Qalam Kendari Integrated Islamic Elementary School as a solution to create a generation that has superior character and integrity. The purpose of this article is to identify effective strategies and methods in developing an Islamic character-based curriculum and to evaluate the results of implementing the curriculum. The research method used is a literature study and a case study involving interviews, observation and documentation at Al Qalam Kendari Integrated Islamic Elementary School which has implemented a character-based curriculum. The results of the study show that the development of an Islamic character-based curriculum at the school has succeeded in creating a learning environment that encourages students to internalize Islamic values and develop superior characters such as integrity, responsibility, cooperation and independence. Implementation of an Islamic character-based curriculum is an effective approach to achieving the goals of Islamic education with integrity and character.